2020
DOI: 10.1063/5.0008998
|View full text |Cite
|
Sign up to set email alerts
|

Transition from snowplow to deflagration mode in a gas-prefilled parallel-plate plasma accelerator

Abstract: The transition from snowplow mode to deflagration mode of a parallel-plate plasma accelerator under gas-prefilled conditions is studied. The accelerator is powered by a sinusoidal-wave power supply with a first half-period current of 24.3 μs. The current distribution of the current conduction channel is measured by magnetic probes, the optical emission spectrum by a spectroscopic system, and the plasma optical intensity by photodiodes. The parallel-plate plasma accelerator does not form a thin current sheet, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For the formation of spheromak, the accelerated plasma needs to compress, stretch the bias magnetic field and complete the magnetic reconnection to finally relax into the spheromak state. Some previous experimental works [21][22][23] have indicated that the evolution of plasma current path in a puffed gas mode is a strong function of the time delay between gas injection and the firing of the capacitor bank to initiate gas breakdown. Snowplow occurs for a long time delay while deflagration occurs for a short time delay.…”
Section: Introductionmentioning
confidence: 99%
“…For the formation of spheromak, the accelerated plasma needs to compress, stretch the bias magnetic field and complete the magnetic reconnection to finally relax into the spheromak state. Some previous experimental works [21][22][23] have indicated that the evolution of plasma current path in a puffed gas mode is a strong function of the time delay between gas injection and the firing of the capacitor bank to initiate gas breakdown. Snowplow occurs for a long time delay while deflagration occurs for a short time delay.…”
Section: Introductionmentioning
confidence: 99%